AB167. The protective effect of KH-204 in androgen-deprived male rat - Bae, Woong Jin (Transl Androl Urol, 2015)
OBJECTIVE: Korean herbal formulation, Ojayeonjonghwan is used to treat male infertility and late-onset hypogonadism (LOH) symptoms including erectile dysfunction (ED). We investigated the antioxidant effects of modified Ojayeonjonghwan, KH-204 in androgen-deprived male rats. METHODS: We investigated either distilled water (sham-operated) or leuprorelin 0.5 mg/kg, which was subcutaneously administered once to the back of rats. Male rats were divided into four groups (n=8 in each): a normal control group, an androgen-deprived control group and two androgen-deprived groups treated p.o. with either 200 or 400 mg/kg, KH-204 for 4 weeks. The testes and epididymides from rats in all groups were removed, weighed and subjected to histological examination and semen analysis after treatment. Oxidative stress was assessed by measuring 8-hydroxy-20-deoxyguanosine (8-OHdG) and superoxide dismutase (SOD). RESULTS: The results showed that KH-204 provided a protective effect against the androgen deficiency. When compared with an androgen-deprived control group, KH-204 treatment significantly increased testis and epididymis weights, improved SOD activity, and raised plasma testosterone levels. It had a dose-dependent protective effect against DNA oxidative damage. CONCLUSION: This study suggests that the antioxidant effect of KH-204 contribute to the improvement of serum testosterone levels. It may be useful in inhibiting the induction of experimental andropause.